—-RETRACTED—- ——–RETRACTED—–AN UNUSUAL PRESENTATION OF STEVEN-JOHNSON SYNDROME AFTER BNT162B2 COVID-19 VACCINATION: RETRACTED (The article has been retracted due to Data Property Issue) - Patel, Ravi; Lu, Victor (Journal of Ayub Medical College Abbottabad, 2023)
——–RETRACTED—– We present a 23-year-old white British male that presented to the Accident and Emergency Department, two weeks after the second dose of the BNT162b2 (BioNTech/Pfizer) vaccine. No similar use has been documented previously in literature. We report one potential complication of the Pfizer COVID-19 vaccine: a known case of Stevens-Johnson syndrome (SJS) that occurred after the second dose of the Pfizer COVID-19 vaccine alone without exposure to any other drug. Despite a significantly severe adverse drug reaction, the patient demonstrated completed recovery. The risk of developing severe cutaneous drug reaction from subsequent COVID-19 vaccinations in these patients is still unclear and remains a dilemma to date.